Biomass of karst evergreen and deciduous broad-leaved mixed forest in central Guizhou province, southwestern China: a comprehensive inventory of a 2 ha plot - Liu, Li-Bin; Wu, Yang-Yang; Hu, Gang; Zhang, Zhong-Hua; Cheng, An-Yun; Wang, Shi-Jie; Ni, Jian (Silva Fennica, 2016)
The biomass of a secondary evergreen and deciduous broad-leaved mixed forest was comprehensively inventoried in a permanent 2 ha plot in southwestern China. Biomass models, sub-sampling, soil pit method, and published data were utilized to determine the biomass of all components. Results showed that the total biomass of the forest was 158.1 Mg ha; the total biomass included the major aboveground (137.7 Mg ha) and belowground (20.3 Mg ha) biomass components of vascular plants as well as the minor biomass components of bryophytes (0.078Â Mg ha) and lichens (0.043Â Mg ha). The necromass was 17.6 Mg ha and included woody debris (9.0Â MgÂ ha) and litter (8.6 Mg ha). The spatial pattern of the aboveground biomass was determined by the spatial distribution of dominant trees with large diameter, tall height, and dense wood. The belowground biomass differed in terms of root diameter and decreased with increasing soil depth. The belowground biomass in each soil pit in local habitats was not related to the spatial distribution of woody plants and soil pit depth. The karst forest presented lower biomass compared than the nonkarst forests in the subtropical zone. Biomass carbon in the karst terrains would increase substantially if degraded karst vegetation could be successfully restored to the forest. Comprehensive site-based biomass inventory of karst vegetation will contribute not only to provide data for benchmarking global and regional vegetation and carbon models but also for regional carbon inventory and vegetation restoration.â1â1â1â1â1â1â1â1